A two-step process for hydrogen production from vacuum residue - Sahu M.K.; Sinha A.S.K. (My University, 2025)
A two-step process has been developed for the conversion of vacuum residue to hydrogen. The first step involves oxidation of the vacuum residue in liquid phase at 373-423 K using ozone. The partially oxygenated products are utilized for hydrogen production by catalytic oxidative steam reforming over 2 wt% Pt/Al2O3-La2O3-CeO2 catalyst. This two-step process reduces the formation of coke on the catalyst surface. Results show that it is a viable and technically feasible method for production of hydrogen from vacuum residue. © 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.